Low cost design of microprocessor EDAC circuit - 郝丽 于立新 彭和平 庄伟 (Journal of semiconductors, 2015)
An optimization method of error detection and correction（EDAC） circuit design is proposed. The method involves selecting or constructing EDAC codes of low cost hardware, associated with operation scheduling implementation based on 2-input XOR gates structure, and two actions for reducing hardware cells, which can reduce the delay penalties and area costs of the EDAC circuit effectively. The 32-bit EDAC circuit hardware implementation is selected to make a prototype, based on the 180 nm process. The delay penalties and area costs of the EDAC circuit are evaluated. Results show that the time penalty and area cost of the EDAC circuitries are affected with different parity-check matrices and different hardware implementation for the EDAC codes with the same capability of correction and detection code. This method can be used as a guide for low-cost radiation-hardened microprocessor EDAC circuit design and for more advanced technologies.